2013
DOI: 10.1002/asia.201201162
|View full text |Cite
|
Sign up to set email alerts
|

Solid‐State Form Screen of Cardiosulfa and Its Analogues

Abstract: Cardiosulfa is a biologically active sulfonamide molecule that was recently shown to induce abnormal heart development in zebrafish embryos through activation of the aryl hydrocarbon receptor (AhR). The present report is a systematic study of solid-state forms of cardiosulfa and its biologically active analogues that belong to the N-(9-ethyl-9H-carbazol-3-yl)benzene sulfonamide skeleton. Cardiosulfa (molecule 1; R(1) = NO2, R(2) = H, R(3) = CF3), molecule 2 (H, H, CF3), molecule 3 (CF3, H, H), molecule 4 (NO2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 102 publications
0
4
1
Order By: Relevance
“…The higher density perhaps arises from the planar conformation in these metastable polymorphs III and IV, which results in a denser packing of molecules. Even though we recently concluded that planar a molecular conformation tends to give low solubility, the present results appear to be an oddity with the planar confirmation and higher density polymorphs III and IV of CLX exhibiting higher solubility. The neutral forms III and IV of CLX transformed to the stable neutral Form I in slurry experiments, whereas zwitterionic Form II and neutral Form I are stable to the same aqueous solution (Figure S5, Supporting Information).…”
Section: Resultscontrasting
confidence: 97%
See 1 more Smart Citation
“…The higher density perhaps arises from the planar conformation in these metastable polymorphs III and IV, which results in a denser packing of molecules. Even though we recently concluded that planar a molecular conformation tends to give low solubility, the present results appear to be an oddity with the planar confirmation and higher density polymorphs III and IV of CLX exhibiting higher solubility. The neutral forms III and IV of CLX transformed to the stable neutral Form I in slurry experiments, whereas zwitterionic Form II and neutral Form I are stable to the same aqueous solution (Figure S5, Supporting Information).…”
Section: Resultscontrasting
confidence: 97%
“…This fluxional change in the clonixin molecule results in conformational polymorphs (see Table for torsion angles and overlay diagram in Figure ) along with the synthon changing from carboxylic acid dimer to acid–pyridine in four polymorphs. The influence of molecular conformation on drug solubility and dissolution rate was discussed in a recent paper: in general, twisted conformation gave a more soluble crystalline form compared to the planar state . The twisted and planar conformations of clonixin polymorphs could tune drug solubility.…”
Section: Resultsmentioning
confidence: 99%
“…39 The authors also mentioned that similar phenomena occur with the crystals of nickellocene and ferrocene-d 10 . In a recent report, Nangia and coworkers 40 mentioned that by dipping in liquid nitrogen, polymorph II of a sulfonamide derivative undergoes crystal disintegration and transforms into a new polymorph III, although this does not happen with polymorph I. Molecules of form I form infinite N-H⋯O catemeric chains whereas form II molecules exist as C-H⋯O hydrogen-bonded (Fig. 9).…”
Section: Mechanical Effect At Low Temperaturementioning
confidence: 99%
“…The list of APIs whose cocrystals or salts have been prepared through LAG is already extensive and is continuously growing (Scheme 1A). It includes sulfadimidine, 104 acetylsalicylic acid, 105 indomethacin, 106 naproxen, 107 salicylic acid, 104 salicylamide, 107 4-aminosalicylic acid, 108 carbamazepine, 105,109 dihydrocarbamazepine, 110 acetaminophen, 111 chloramphenicol, 112 artemisinin, 113 lenalidomide, 114 niclosamide, 115 felodipine, 116 stanozolol, 117 b-estradiol, 118,119 progesterone, 119 tenoxicam, 120 meloxicam, 121 aripiprazole, 122 telaprevir, 123 ezetimibe, 124 diflunisal, 125 diclofenac, 125 bumetanide, 126 gabapentin, 127 isoniazid, 128 blonanserin, 129 temozolomide, 130 aceclofenac, 131 curcumin, 132 meclofenamic acid, 133 pyrimethamine, 134 sildenafil, 135 piracetam, 136 cardiosulfa, 137 tadalafil, 138 trospium chloride, 12b flurbiprofen, 139 biclotymol, 65 ibuprofen, 84a,140 and more. Whereas most literature reports of mechanochemical API cocrystallisation are dedicated to the discovery of new solid forms and/or modification of solid-state API properties, there is also an extensive body of work dedicated to model API systems (Scheme 1B), such as caffeine,…”
Section: Api Cocrystal and Salt Formationmentioning
confidence: 99%